Correction: The side effects of platinum-based chemotherapy drugs: a review for chemists. Issue 23 (29th May 2018) - Oun, Rabbab; Moussa, Yvonne E.; Wheate, Nial J.
Abstract : Correction for 'The side effects of platinum-based chemotherapy drugs: a review for chemists' by Rabbab Oun et al., Dalton Trans., 2018, 47, 6645–6653.